Cardiac toxicity after treatment for childhood cancer - Bricker, J. Timothy; Green, Daniel M; D'Angio, Giulio J (Wiley-Liss, 1994)
Texas Children\'s Hospital, Houston, Texas. Papers presented at the Second International Conference on the Long-Term Complications of Treatment of Children and Adolescents with Cancer, June 12-14, 1992, Buffalo, New York. 32 U.S. contributors.
Keywords: antracykliny; Neoplasms; nádory; Heart; srdce; Medication Therapy Management; Child; Infant; management farmakoterapie; dítě; pediatrie; kojenec; Anthracyclines; farmacie a farmakologie; radioterapie; Radiotherapy; kardiologie; onkologie